Weaving threads of care: Examining extended family support for aging in rural Ghana - Amos (Magyar Gerontológia, 2025)
Globally, societies are experiencing a significant increase in the population of older adults, a demographic shift that presents both opportunities and challenges. This transformation is particularly pronounced in developing countries such as Ghana.